Las aplicaciones de las tecnologías de la información y comunicación y su incidencia en los aprendizajes significativos en la asignatura de matemática, en el segundo ciclo de la carrera de Ingeniería de Medio Ambiente de la Universidad Técnica de Cotopaxi; en el período octubre 2014 a febrero 2015. propuesta de estrategias metodológicas de tecnologías de la información y comunicación para el docente - Toapanta Cali, Blanca Patricia (2015)
This work permits to determine how the applications of information and communication technology affect meaningful learning in the subject of Mathematics, so it’s analyzed the use of equipment, tools and applications of Information and Communication Technology as elements which deal with the training of students according to new approaches in higher education, this means that teachers and students are constantly updated about technological advances applicable for the training and the teaching-learning process.